Cytotoxic effects of cleansing solutions recommended for chemical lavage of pulp exposures - Costa, CAS; Edwards, C. A.; Hanks, C. T. (Mosher & Linder, Inc, 2001)
Purpose: To evaluate the in vitro cytotoxic effects of three cleansing solutions used for chemical lavage of pulp exposures. Materials and Methods: the immortalized odontoblast cell line (MDPC-23) was plated (30,000 cells/cm(2)) and incubated for 72 hrs in 24-well dishes. After counting the cell number under inverted light microscopy, 20 mul of the experimental and control solutions were added to 980 mul of fresh culture medium. Then, hydrogen peroxide (3%, H2O2), sodium hypochlorite (6%, NaOCl) or calcium hydroxide-saline solution (5g of Ca(OH)(2) in 10 mi of sterile distilled water) were added to wells for experimental Groups 1, 2 and 3, respectively. The positive and negative control groups received Syntac Sprint bonding agent (SS) and phosphate buffered saline (PBS), respectively. Following incubation for 120 min the cell number was counted again, the cell morphology was evaluated by scanning electron microscopy (SEM) and the cell metabolism was determined by the methyltetrazolium (MTT) assay. The scores obtained from cell counting and MTT assay were analyzed with an ANOVA followed by Fisher's PLSD tests. Results: H2O2 NaOCl solutions, and SS bonding agent were more cytotoxic than Ca(OH)2 or PBS. In the groups with H2O2 Or SS, only a few cells remained attached to the bottom of wells. The difference between these two groups was not statistically significant. H2O2, NaOCl and SS depressed the mitochondrial enzyme response by 97.7%, 97.3%, and 95.0%, respectively. on the other hand, Ca(OH)2 depressed the metabolic activity of cells by only 5%. While H2O2, NaOCl and SS caused extreme changes on the cell morphology, neither Ca(OH)2 nor PBS promoted dramatic changes in the cell morphology.